Experimental investigation of the combustion of bituminous coal in air and O2/CO2 mixtures: 2. Variation of the transformation behaviour of mineral matter with bulk gas composition - Zhang, L.; Jiao, F.; Binner, E.; Bhattacharya, S.; Ninomiya, Y.; Li, Chun-Zhu (Elsevier Science Ltd, 2011)
Combustion of a Chinese bituminous coal was carried out in a laboratory-scale drop tube furnace (DTF) to clarify the variation of ash properties with bulk gas composition. The combustion conditions tested include three bulk gases, air, 21% O2/79% CO2 and 27% O2/73% CO2, two furnace/gas temperatures close to the fluidized bed reactor temperature range, 1073 K and 1273 K, and three particle residence times. Apart from bulk properties analysis, individual ash particles and the original mineral species in coal were characterized using Computer – Controlled Scanning Electron Microscopy (CCSEM). The results indicate that, under the given experimental conditions, shifting bulk gas from air to O2/CO2 mixtures is insignificant in terms of the elemental composition of bulk ash, in agreement with the literature. However, changes in the properties of individual species/metals are noticeable, including the extent of the vaporization of volatile elements, ash particle-size distribution (PSD), crystallization extent of K alumino-silicate associate, pyrite decomposition and oxidation rate and formation propensity of liquidus in ash. These changes were mostly considered to be caused by the evolution of included mineral grains in the distinct char particles in the O2/CO2 environment. Reduction in char particle temperature with bulk gas shifting from air to O2/CO2 mixtures was primarily crucial, which, however, could be overweighed by the existence of a fairly strong local reducing condition on the char surface in O2/CO2. Consequently, vaporization of the volatile elements such as Na and P was promoted; formation of the crystalline leucite in air was in contrast inhibited. Furthermore, the extent of coalescence of included minerals and oxidation rate of pyrite (or its derivative, pyrrhotite) were also influenced by char consumption rate, i.e. the receding extent of char surface. These parameters exerted a combined effect on ash formation, requiring detailed mathematical modeling to describe the dynamics of the formation of oxy-fuel ash. This study also indicated that the differences of ash properties formed between air and O2/CO2 mixtures can be greatly reduced and eventually eliminated by increasing furnace temperature. Increase in the turbulence of gas flow should also benefit the elimination of the side effects of local reducing gases on char surface.